Viability Assessment of Small-Scale On-Grid Wind Energy Generator for Households in Malaysia - Gamal Alkawsi; Yahia Baashar; Ammar Ahmed Alkahtani; Chin Wai Lim; Sieh Kiong Tiong; Mohammad Khudari (Energies, 2021)
This study provides a techno-financial evaluation of two sites in Malaysia: Kudat, located on the coast of the northernmost part of Sabah, the state of East Malaysia with promising wind potential, and Putrajaya in the Klang Valley region with moderate wind potential at high elevations similar to the dominant cities in Malaysia. Three small-scale wind turbines were evaluated, taking into account a nominal electrical power generation below 100 kW. The research is focused on 220 residential households. The software used to perform the evaluation was Hybrid Optimization of Multiple Energy Resources (HOMER). The research novelty is the examination of the non-hybrid small-scale turbines at high elevations for regions with low wind speed, such as Malaysia. Regardless of the wind farms’ financial profit, this study used the net present cost (NPC) analysis in all cases. This research demonstrates the feasibility of small-scale wind turbines mounted at high elevations for generating sufficient energy. The results indicate that in both areas, the RX-20KH3 model is the best option, and the costs of the FH-5000 and RX-20KH3 farms are proportionate for a renewable project. Furthermore, with government support, the WES80 farm could be suitable.